The hungry coat : a tale from Turkey - Demi (Margaret K. McElderry Books, 2004)
After being forced to change to a fancy new coat to attend a party, Nasrettin Hoca tries to feed his dinner to the coat, reasoning that it was the coat that was the invited guest.